NAD+ metabolism is a key modulator of bacterial respiratory epithelial infections - Björn Klabunde; André Wesener; Wilhelm Bertrams; Isabell Beinborn; Nicole Paczia; Kristin Surmann; Sascha Blankenburg; Jochen Wilhelm; Javier Serrania; Kèvin Knoops; Eslam M. Elsayed; Katrin Laakmann; et al. (Nature Communications, 2023)
Abstract Lower respiratory tract infections caused by Streptococcus pneumoniae (Spn) are a leading cause of death globally. Here we investigate the bronchial epithelial cellular response to Spn infection on a transcriptomic, proteomic and metabolic level. We found the NAD+ salvage pathway to be dysregulated upon infection in a cell line model, primary human lung tissue and in vivo in rodents, leading to a reduced production of NAD+. Knockdown of NAD+ salvage enzymes (NAMPT, NMNAT1) increased bacterial replication. NAD+ treatment of Spn inhibited its growth while growth of other respiratory pathogens improved. Boosting NAD+ production increased NAD+ levels in immortalized and primary cells and decreased bacterial replication upon infection. NAD+ treatment of Spn dysregulated the bacterial metabolism and reduced intrabacterial ATP. Enhancing the bacterial ATP metabolism abolished the antibacterial effect of NAD+. Thus, we identified the NAD+ salvage pathway as an antibacterial pathway in Spn infections, predicting an antibacterial mechanism of NAD+.